Genebank Operation in the Arena of Access and Benefit-Sharing Policies - Brink, Martin; van Hintum, Theo (Frontiers in Plant Science, 2020)
Since the 1990s, the exchange of genetic resources has increasingly been regulated. The Convention on Biological Diversity (CBD), the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA) and the Nagoya Protocol recognized the national sovereign rights over genetic resources, and provided a framework for domestic legislations on Access and Benefit-Sharing (ABS). As each country can follow its own interpretations and procedures, this has led to a complex situation, resulting in restricted access to genetic resources and limited benefit-sharing, effects contrary to the objectives of these agreements. Although the Multilateral System of the ITPGRFA provides opportunities for facilitated access to plant genetic resources for food and agriculture (PGRFA), plant genebanks too face increasing complexity in their operation. Adding material to genebank collections has become more difficult, not only because collecting missions need to be negotiated with national and local authorities, but also because taking over material from other collections is only possible if the origin of the material is properly documented and complies to the rules. Providing access to their own collections is only possible when distribution complies with the conditions under which the material was received and the national laws of the country where the genebank is located. The only way genebanks can deal with this new complexity, apart from stopping to add or distribute material, is by setting up proper procedures to document the origin of every accession and the conditions for its use and further distribution. To prevent a further decrease in access to PGRFA, complexity has to be fought. Applying only the Standard Material Transfer Agreement (SMTA) of the ITPGRFA, even for material that does not fall under the ITPGRFA, would simplify matters. The scope of the ITPGRFA could be expanded to include all crops, and certain unclarities (for instance regarding in situ material and wild species) could be resolved. Finally, compliance to the ITPGRFA should be improved and better monitored.